Relationships between Perturbations of a Linear Relation and Its Operator Part - Guixin Xu; Meirong Zhang (Discrete Dynamics in Nature and Society)
In this study, we establish some relationships between perturbations of a linear relation and its operator part by constructing an operator, which is induced by two linear relations including their closedness, hermiticity, self-adjointness, various spectra, defect indices, and perturbation terms.